L’échelon manquant ? Les archives municipales en Algérie : histoire de fonds et possibilités historiographiques - Thierry Guillopé (L’Année du Maghreb)
Following in the footsteps of others, this article focuses on the history of municipal repositories in Algeria, presenting the archives they contain and the avenues of research they open up. More generally, it follows in the footsteps of a growing body of work that closely combines archival and historical considerations. On the one hand, thinking about archives and colonial or imperial dynamics together has been the subject of particularly stimulating research, both across the board and in more specific fields. Secondly, “urban archives” are a research subject in their own right. Research into the history of Algeria in the 19th and 20th centuries is in the process of renewal. The documents on which they are based were produced by a wide variety of individuals and institutions. They are currently scattered, for the most part, between Algeria and France. However, the papers produced by the municipalities are still missing. This is why their identification, description and analysis are inseparable from a history of their archiving (Bloch, 1932). The challenge is not just to explore these collections; it is also to understand how they are preserved, destroyed and filed, so as to better define their historiographical interest.A brief history of archival culture in Algeria, from 1830 to the present day, is the first stage in these reflections. The individuals responsible for municipal papers, all of whom are still unknown to historiography, are highlighted here. The importance of their networks and training on their archival practices is examined. The same applies to the storage locations and successive moves that form the material framework for preservation. These individuals, places and practices are captured in a myriad of traces scattered between Algeria and France. The archives of the departments responsible for preserving the collections form one of the essential sources for this work. They consist of annual reports from the curators, inspection reports from their supervisors and deposit slips. All these documents provide a wealth of information for understanding the “archiving process” (Chabin, 2021). Municipal newsletters, directories and administrative reports also help us to understand the places, players and institutions involved. In addition, the press is used to shed light on various events and trajectories that are essential to understanding this history.The archives of the communes of the wilaya of Algiers are then examined in greater detail. It highlights the new regulations governing them, their conditions of access, the state of the collections and their place in a longer history. The article also reports on the results of the major archival work carried out on these collections by Aïcha Mati (2013) in Arabic, as has been the case for the most part since the 2000s. The author carried out a large number of internships, interviews and questionnaires with around fifty archive departments and the secretaries-general of the Assemblées Populaires Communales (APCs). The results of this survey show that the situations vary significantly: there are differences in the volumes conserved, in the chronological ranges covered, in the physical condition of the archives and repositories, and in the degree of progress made in filing.The third part of this study concludes with a presentation of the archive’s holdings. Their interest lies not least in helping to fill in some of the blind spots in historiography. They would enable us to undertake a history of urban property and neighbourhood social life, agricultural practices, justice, etc. Above all, the collections held by the municipalities enable us to get as close as possible to everyday life. In this respect, they provide a focus for observation that complements that provided by other, better-known or more widely-used sources (archives from the prefectural or gubernatorial administration, the writings of notables, etc.).So, from Oran to Annaba via Algiers, as well as in smaller towns, this article is an invitation to discover the municipal archives. Examined in the light of old and new questions, and provided that researchers are allowed access to them, they could well help to revitalise the writing of Algerian history.